Highly activated carbon enterosorbent mediates the suppression of paraneoplastic syndrome associated with lewis lung carcinoma in mice - Sarnatskaya, V.V.; Sakhno, L.A.; Paziuk, L.M.; Yushko, L.A.; Rodionova, N.K.; Maslenny, V.N.; Sydorenko, A.S.; Nikolaev, V.G. (Experimental Oncology, 2018)
Aim: To investigate the effect of enterosorption on the development of paraneoplastic syndrome in mice with Lewis lung carcinoma (LLC). Materials and Methods: The study was performed on male С57/ВL6 mice with transplanted LLC. As an enterosorbent, highly activated powder fraction of HSGD was administered per os daily at a dose of 0.625 g/kg for two weeks starting from the 7th day after tumor cell transplantation. Analysis of hemo- and myelograms, morphological alterations in vital organs, the activities of catalase and superoxide dismutase, biochemical analysis of blood and quantitative analysis of hydroperoxides, malonic dialdehyde, аdvanced oxidation protein products was carried out by standard methods after completing the course of enterosorption. Ligand loading of blood plasma proteins was estimated by the method of differential scanning microcalorimetry. Results: Administration of enterosorbent resulted in inhibition of LLC growth and in nearly 2-fold decrease of lung metastases number (p < 0.05). Activation of granulocytic line in the bone marrow with nearly 3-fold enhancement of mitotic activity took place after enterosorbent administration. Red cell lineage indices and bone marrow cellularity remained unaltered. After enterosorption session, the studied biochemical indices of peripheral blood evidenced on decreasing the endogenous intoxication and oxidative stress levels, improving the functional state of kidneys, increasing the resistance of erythrocyte membranes and lowering the ligand loading of blood plasma transport proteins. Morphological structure of kidneys and liver confirmed significant positive effect of enterosorption. The data of morphologic examination of gastric fundus, small intestine, and large bowel slides after 2-week administration of enterosorbent showed its high safety and proper evacuation from intestine. Conclusion: The two-week long enterosorption session in mice with LLC caused the suppression of tumor growth and metastasis, normalization of bone marrow hemopoiesis. Enterosorption exerted a positive influence on the structural-morphologic indexes and regenerative potential of kidneys and liver, mitigated manifestations of oxidative stress, decreased the level of endogenous intoxication, promoted deliganding of albumin molecule and deloading of erythrocyte membranes.